2014
DOI: 10.3747/co.21.1657
|View full text |Cite
|
Sign up to set email alerts
|

Potential Drug Interactions in Patients with a History of Cancer

Abstract: Background: Cancer survivors (css) are frequently exposed to polypharmacy, which might increase their risk of drug interactions. Our study aimed to determine the relative prevalence of potential drug interactions (pdis) among css compared with non-cancer respondents (ncrs). Methods: Self-reported prescription data from 4975 patients were extracted from the U.S. National Health and Nutrition Examination Survey and screened for pdis using iFacts: Drug Interaction Facts (Facts and Comparisons, St. Louis, MO, U.S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
3
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
4
5
3
2
Order By: Relevance
“…Another study from Netherland reported a prevalence rate of 46% among patients using oral anticancer drugs [41]. Whereas, a study from the United States of America reported 40% prevalence rate of pDDIs [29]. Similarly, the prevalence rate of present study is higher in comparison with studies from other specialties such as internal medicine (52.8%) [25], psychiatry (64.8%) [42], pediatrics (25.8%) [43] and pulmonology (45%) [44].…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Another study from Netherland reported a prevalence rate of 46% among patients using oral anticancer drugs [41]. Whereas, a study from the United States of America reported 40% prevalence rate of pDDIs [29]. Similarly, the prevalence rate of present study is higher in comparison with studies from other specialties such as internal medicine (52.8%) [25], psychiatry (64.8%) [42], pediatrics (25.8%) [43] and pulmonology (45%) [44].…”
Section: Discussioncontrasting
confidence: 59%
“…DDIs among cancer patients have been well studied in developed countries [20,24,[26][27][28][29]. However, such studies have been poorly addressed in developing countries like Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…Another study from Netherland reported a prevalence rate of 46% among patients using oral anticancer drugs [34]. Whereas, a study from the United States of America reported 40% prevalence rate of pDDIs [35]. Similarly, the prevalence rate of present study is higher in comparison with studies from other specialties such as internal medicine (52.8%) [25], psychiatry (64.8%) [36], pediatrics (25.8%) [37] and pulmonology (45%) [38].…”
Section: Discussioncontrasting
confidence: 59%
“…However, it should be noted that the studies differed in trial design, methodology, and, importantly, definitions of DDIs. To avoid harmful DDIs, the following are strongly recommended: a routine reassessment of all prescription and over-the-counter medications and herbal supplements; communication of a complete list of medications between healthcare providers on every referral, hospital admission, hospital transfer, and hospital discharge; and monitoring for signs of DDIs [46,49,50]. However, the optimal approach for screening for DDIs (e.g., comprehensive medication review by a clinical pharmacist, consultation with a clinical pharmacologist, use of clinical decision support software) remains to be determined [43].…”
Section: Polypharmacy and Drug-drug Interactionsmentioning
confidence: 99%